Monocyte subsets display age-dependent alterations at fasting and undergo non-age-dependent changes following consumption of a meal - Ryan G. Snodgrass; Xiaowen Jiang; Charles B. Stephensen (Immunity & Ageing, 2022)
Abstract Background Monocytes are a heterogenous population of immune cells whose subsets and functions become substantially dysregulated with advanced age. Although much of our current understanding of the age-related changes in monocytes is derived from fasting blood samples, most people are predominately in the postprandial state during waking hours. As hormonal, metabolic, and immunological changes in response to the consumption of a meal are manifested in postprandial blood, it’s unclear how age-dependent changes in peripheral monocytes at fasting are impacted by a dietary challenge. Objective We investigated the impact of age and meal consumption on circulating monocyte frequencies and subsets defined as classical (CD14 + CD16-), intermediate (CD14 + CD16 +), or non-classical (CD14dim CD16 +) in a cohort of 349 healthy adult volunteers grouped into categories based on their age: young adults (18–33 y, n = 123), middle adults (34–49 y, n = 115), and older adults (50–66 y, n = 111). Results Following 12-h fast total monocyte counts inversely correlated with subject age. Older adults had significantly fewer circulating monocytes along with elevated levels of TGs, cholesterol, glucose, IL-6, IL-8, TNF, neopterin, and CCL2 compared with young adults. Circulating monocyte pools in older adults consisted of smaller proportions of classical but larger proportions of intermediate and non-classical monocytes. Proportions of classical monocytes were inversely correlated with plasma TNF, IL-8, and neopterin while intermediate monocytes were positively correlated with plasma IL-6, TNF, and neopterin. Three hours after consuming a fat-containing meal postprandial monocyte counts increased in all age groups. Despite age-dependent differences in monocyte subsets at fasting, consumption of a meal induced similar changes in the proportions of classical and non-classical monocytes across age groups. Within the circulating postprandial monocyte pool, percentages of classical monocytes decreased while non-classical monocytes increased. However no change in precursory intermediate monocytes were detected. Our study confirms that ageing is associated with changes in monocyte frequencies and subsets and shows that consuming a fat-containing meal induces temporal changes in monocyte frequency and subsets independently of subject age. Clinical trial Registered on ClincialTrials.gov (Identifier: NCT02367287)